Cinnamic Acid Derivatives as α-Glucosidase Inhibitor Agents - Teni Ernawati; Maksum Radji; Muhammad Hanafi; Abdul Mun’im; Arry Yanuar (Indonesian Journal of Chemistry, 2017)
This paper reviews biological activity of some cinnamic acid derivative compounds which are isolated from natural materials and synthesized from the chemical compounds as an agent of α-glucosidase inhibitors for the antidiabetic drug. Aegeline, anhydroaegeline and aeglinoside B are natural products isolated compounds that have potential as an α-glucosidase inhibitor. Meanwhile, α-glucosidase inhibitor class of derivatives of cinnamic acid synthesized compounds are p-methoxy cinnamic acid and p-methoxyethyl cinnamate. Chemically, cinnamic acid has three main functional groups: first is the substitution of the phenyl group, second is the additive reaction into the α-β unsaturated, and third is the chemical reaction with carboxylic acid functional groups. The synthesis and modification of the structure of cinnamic acid are very influential in inhibitory activity against α-glucosidase.